Synergistic effects of Trichoderma and biochar on the biocontrol of two soil-borne phytopathogens in chickpeas - Kumari, Ranjna; Kumar, Vipul; Koul, Bhupendra; Abul Farah, Mohammad; Mishra, Awdhesh Kumar (Frontiers in Microbiology, 2025)
IntroductionThis study aims to identify and characterize four Trichoderma isolates using molecular techniques, Fourier transform infrared spectroscopy (FTIR), and volatile organic compounds (VOC) profiling.MethodsThe antagonistic activity of these isolates was assessed against Fusarium oxysporum f. sp. ciceri (FOC) and Sclerotium rolfsii (SR) using a dual culture technique. The synergistic effect of Trichoderma harzianum (accession no. PP256488) combined with biochar (BC) was evaluated for plant growth enhancement and disease suppression. Four Trichoderma isolates (T. harzianum, T. asperellum, T. virens, and T. lixii) were identified through ITS region analysis, VOC profiling, and FTIR spectroscopy.ResultsMolecular analysis confirmed their distinct identities, and GC-MS analysis revealed 37 VOCs out of 162 with antipathogenic properties. Unique FTIR peaks were recorded at 3271.96 cm−1 for T. virens, 2800–2900 cm−1 for T. asperellum, and 2850–2950 cm−1 for both T. lixii and T. harzianum. Scanning electron microscopy (SEM) analysis of T. harzianum revealed mycoparasitic structures, including hyphal coils, penetration holes, and appressoria, indicating effective pathogen interaction. The combined application of Trichoderma and biochar (T9) significantly enhanced root length (9.23 cm), plant height (26.03 cm), and root mass (43.33 g) in chickpea plants. Moreover, treatments (T9) and (T10) reduced the disease incidence in chickpeas, decreasing fusarium wilt by 27% and collar rot by 33%, respectively.ConclusionThis sustainable approach exhibits the potential of combined application of Trichoderma and biochar which can enhance plant growth and reduce disease incidence, and improve food security.